ANALISIS PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN ANTAR PROVINSI DI INDONESIA TAHUN 2004-2010 - Rita Sari, Norma; Pujiyono, Arif (Diponegoro Journal of Economics, 2013)
Throughout Indonesia's economic growth is relatively increased. During 2004-2010 its growth decreased in 2009 due to the impact of the global economic crisis. On the other side, the income gap between regions is caused by the concentration of a regional investment. This research purposed to determine how much inequality between provinces in Indonesia, and to determine the leading sectors in each of 33 provinces in Indonesia so that economic growth can be achieved optimally. The analytical method used was the analysis of economic growth, location quotient (LQ), Shift-share, Klassentypology, Williamson index and inverted U hypothesis.Results of this research showed that: the service and agriculture sectorincluding within the potential sectors to promote economic growth in each province in Indonesia. There still provinces of Indonesia which were classified in the relatively backward province, there are 14 provinces including the relatively backward regions. Income disparities between provinces in Indonesia in 2004-2010 is high (> 0.5) and had declined tendency. While the Kuznetsâ€™inverted â€œUâ€ hypothesis which describes the relationship between growth and inequality prevailing in the Province of Indonesia.Based on these findings suggestions which could be submitted for the development of inter-provincial inequality in Indonesia is implementing development policies that prioritize the still relatively backward provinces without disregardupon the developed provinces which grown rapidly.